PERMAINAN BERBASIS KECERDASAN MAJEMUK DALAM PENDIDIKAN JASMANI ANAK TAMAN KANAK KANAK - Febrita P. Heynoek, (Ordik, 2012)
Learning can be strated as a great endeavour in creating best situation and condition intended to motivate student to learn. Multiple intelligence theory proposed by Howard Gardner provided a different nuance in learning since it tries to optimize the intellegence of the students. The implementation of this theory in the teaching of physical education in kindergarten had brought out some serious problems, particularly the difficulties of the teachers in implementing it on field game format.